THE PERSONAL COMPONENT OF INDIVIDUAL EXPERIENCE FORMATION IN TRAINING WORK AS A WAY TO A MORE POSITIVE SELF-CONCEPT IN THE CONTEXT OF PERSONAL IDEAS ABOUT WELL-BEING GENERALIZATION - Севост`яновПавло Олександрович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The basis of the training program is the conclusion that there is a direct connection between the openness to experience with the idea of oneself as a sensitive, independent, successful, carefree and optimistic person, as well as - the opposite with the idea of ​​oneself as a tough person in the past, present and future. There is also a opposite connection between the openness to experience and the perception of oneself as an anxious person, but it applies only to the present and the future. The connection between openness of experience and ideas about one’s own security and self-confidence is observed only in relation to the past and present. In addition, the openness of the experience is characterized by a direct relationship with such indicators of self-regulation as modeling, flexibility, independence and its integral level; the locus of control "Me", the general meaning of life, and the level of significance of the values ​​of independence and stimulation; and opposite - with the locus of control over life and the level of significance of the values ​​of conformity, traditions, power and security. Based on these findings, a training program was developed and tested, which provided for the development of creative thinking, personal growth, strengthening mental health and the development of meaning awareness. During the development of the program, it was taken into account that under conditions of significant socio-political changes there is a decrease in such components of personal experience as locus of life control, general meaningfulness of life, as well as growth of values ​​such as independence, stimulation, hedonism, achievement and power. The approbation of the training program revealed significant changes towards the positive dynamics of the vast majority of indicators in all three time dimensions, which indicates that, first, our established patterns of functioning of the personal experience depending on “Myself-wellbeing” and the impact of socio-political changes are correct; secondly, that the training program of forming the elements of the personal component of individual experience in the training process as a way to increase the well-being reflected in the self-concept is effective. On the basis of the pilot training work, recommendations were formulated on the formation of elements of the personal component of individual experience in the training process as a way to increase well-being, reflected in the self-concept.